Effect of the addition of brazilian red propolis extract in ground beef (Research, Society and Development, 2021)
Meat has important nutritional characteristics for the diet, being a source of high biological value animal protein, and containing important vitamins for the organism. Ground beef is one of the most consumed meat products, which has an increased surface area, and also a high potential for inadequate storing conditions, which reinforces the relevance of innovative technologies for its preservation, such as the use of propolis – a highly diversified product with antimicrobial and antioxidant activities, seen as a component capable of prolonging shelf life. This study evaluated the effects of the addition of Brazilian red propolis extract to ground beef as a natural antioxidant for 0, 7, 14 and 21 days of storage at a temperature of 7 ºC. The physicochemical parameters of water, protein, lipids and ash content remained stable until the 14th day of storage, while the microbiological ones presented peaks of contamination by Coliforms at 35 and 45 ºC in the same period, however, the absence of Salmonella sp/25g in the meat analyzed, made it suitable for human consumption, thus confirming the effectiveness of using red propolis extract in its conservation.